Wasted sludge treatment contributions in the WWTP total cost - Espírito Santo, I. A. C. P. (2007)
This paper aims to analyze the cost contribution of a simple wasted sludge process in the WWTP design total cost. The plant design relies on a combined ATV and double exponential model to describe the secondary settler as well as on a simple sludge treatment based on dewatering followed by deposition in landfills. The experiments carried out with three small WWTPs in design show that the chosen wasted biosolids treatment is responsible for 10 to 14% of the total costs. However significantly higher values are obtained when the secondary settler is described by an ATV model.